Vision-based fringe projection measurement system for radial vibration monitoring of rotating shafts. (1st December 2022) - Zhong, Jianfeng; Liu, Dongming; Chi, Shoujiang; Tu, Zhao; Zhong, Shuncong
Highlights: A vision-based fringe projection shaft radial measurement system was proposed. A novel one-dimensional operation algorithm for the calculation of 2D radial displacements was proposed. The shaft radial displacements can be simultaneously measured with high accuracy using one camera. Abstract: Shaft radial vibration signals of rotary machines are crucial dynamic information for condition monitoring and fault diagnosis. A novel vision-based fringe projection vibration measurement system is proposed to monitor the radial displacements of a rotating shaft. The fringe pattern was projected on the surface of the shaft and the deformed fringe was acquired by a high-speed camera. A novel fringe processing algorithm was proposed to extract the radial displacement with good accuracy and efficiency. The vertical displacement could be obtained by locating the symmetric center of the recorded fringe. Meanwhile, the horizontal displacement could be obtained from the shift of the fringe at the symmetric center. The influence factors affecting measurement performance were analyzed. Simulations and comparative experiments were carried out for the verification of the feasibility and reliability of the proposed system. Comparing with the multiple eddy current sensors based system, the proposed method can realize multi-dimensional vibration measurement using one camera. The merits of simple in system, easy in operation, high accuracy and effectiveness in measurement make it attractive for dynamic characterization, condition monitoring and faults diagnosis of rotating machineries in actual applications.